Giving voice to the voiceless: connecting graduate students with high school students by incubating DRR plans through participatory mapping - Trejo-Rangel, Miguel Angel; Mota Ferreira, Adriano [UNESP]; Marchezini, Victor; Rodriguez, Daniel Andres; Oliveira, Melissa da Silva; Messias dos Santos, Daniel (Emerald, 2022)
Purpose: The purpose of this study is to encourage graduate students to facilitate a participatory mapping activity with high school students, to have their voices heard in the disaster risk reduction (DRR) agenda. Design/methodology/approach: A participatory mapping, youth-led session, was conducted with 22 high school students, where they had to identify flood and landslide-prone areas. Then, they were asked to propose and plan DRR measures in collaboration with local partners in São Luiz do Paraitinga, Brazil. Findings: The participatory method engaged the graduate students and the high school students in the DRR debate, allowing them to map hazards and vulnerabilities, and to discuss five incubation projects for enhancing DRR in the city. Originality/value: This research highlights the importance of involving young people in DRR formulation and planning to build local capacities in younger generations. The outputs were shared with the local civil defense and a local non-governmental organization (NGO), who suggested recommendations to improve the five incubation projects.
Keywords: Capacity building; Education; Graduate students; High school; Leadership; Social participation